STRATEGI BADAN PERTANAHAN NASIONAL KOTA PEKANBARU DALAM MEMINIMALISIR PERMASALAHAN TUMPANG TINDIH SERTIFIKAT TANAH (OVERLAPPING) DI KOTA PEKANBARU - Siti Hardianti Rukmana Manurung; Abdul Sadad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
Certificate of land said to be evidence of a legitimate legal ownership. But in fact it is still often the case of overlapping land certificates among the community. All started from the increasing of need the land so that people trying to gain ground in various ways even with other people's land grab. In addition causes the occurrence of overlapping land certificate arising from the national land Agency parties city of Pekanbaru that do land registration system that is sporadic and manual, the lack of transparency towards land ownership also be the cause.The purpose of this research is to find how strategy national land agency the city of pekanbaru in minimizing the problem overlapping land certificates in pekanbaru and knows factors affecting strategy national land agency the city of pekanbaru in minimizing the problem overlapping land certificate in pekanbaru. The study is done by using the method the qualitative study, with study data is descriptive. In data collection, researchers used technique interview, observation, literature and documentation.This research result indicates that strategy land agency the city of pekanbaru not run optimally. Strategy is not was fully exist. such as innovation strategy, the national land agency do not have it even the implementation of the strategy technology just that is said to ease services to the community has not been fully can be done due to the limited application usage online services that available and operating strategies are still lacking. Factors affect the implementation of the strategy is the human resources owned inadequate, the national land agency only held a meeting to keep coordinated, the absence of socialization schedule from the national land agency directly to the community and community participation is still lacking because delivery of program from the national land agency yet optimal.Key words : Strategy, Certificate of land, Overlapping